Focusing on the object of learning and what is critical for learning: a case study of teachers’ inquiry into teaching and learning mathematics - Runesson, Ulla (Faculty of Education, University of the Free State, 2013)
During the last decade, Lesson Study, a Japanese professional development model involving a community of learners, has been spreading to countries around the world. Lesson Study is a systematic process of inquiry into classroom practices where teachers collaborate in planning, implementing, observing and revising lessons. The approach used in the study reported in this paper involves a version of Lesson Study, namely Learning Study. Whereas the underpinning theory in Lesson Study is often implicit, Learning Study has an explicit theory that can help teachers to pedagogically theorise about their practice, students’ learning and the object of learning. Through one Swedish Learning Study in mathematics, I demonstrate what teachers can learn by exploring what is critical for their students’ learning and how teaching can be improved to enhance learning.
Keywords: Lesson Study; Learning Study; Teaching algebra; Teacher learning; Variation theory